The report on sustainable development and investments in the agricultural sector: The environmental capital perspective - Volodymyr Metelytsia; Taras Gagalyuk; Olena Kolisnyk (2024)
Ukrainian agribusiness works in challenging conditions today, and the international community greatly supports it. The decision to grant Ukraine the status of a candidate for EU accession, adopted by the European Council in June 2022, and initiatives such as the provision of financial assistance under the Ukraine Facility program (June 2023) opened up new opportunities for the agricultural sector of Ukraine. The realization of these opportunities depends not only on Ukraine's ability to carry out reforms in the direction of European integration but also on the readiness of business entities to overcome the consequences of hostilities through recovery and reconstruction. Purpose. The article aims to provide scientific justification for the standardized forms of the Report on Sustainable Development and Investments (ESGI-report) in the agricultural sector of the economy for the preparation and publication of environmental capital indicators. Methods. The methods of induction and deduction, analysis, and synthesis formed the basis for developing environmental indicators for the ESGI report. The abstract-logical method became the basis for the study of the norms of European legislation and the leading systems for measuring sustainable development. The analogy method made it possible to propose indicative (reference) indicators for measuring sustainable development at the micro level. Results. The article systematizes the estimated and verifiable indicators of ecological capital. The first group includes risks and opportunities connected with climate change, the transition to sustainable technologies, and martial law. The second group comprises indicators that can be accurately measured with the help of calculators and technical means. They are related to the use of natural resources and the impact on the environment. To prepare the ESGI report, it is proposed that all materials posted on the Sustainable Reporting Platform (SR platform) be used: reporting forms, survey questionnaires, video recordings, as well as materials of webinars, presentations, and articles. The SR platform was developed within the framework of the MSCA4Ukraine program funded by the European Union. Conclusion. Attracting foreign investments for the post-war reconstruction of Ukraine's agribusiness is impossible without preparing and disclosing non-financial information about environmental capital at the micro level. One of the tools for disclosing such information is the ESGI report, which is posted on the SR platform. It is advisable to publish environmental indicators in standardized reporting forms to ensure their comparability with the data of other enterprises. At the same time, to assess the level of sustainable development, it is necessary to apply scientifically based reference values, which are based on best practices, statistical data and the company's own experience. – – , . , 2022 , , Ukraine Facility ( 2023 ), . , ' . – ESGI- (Report on Sustainable Development and Investments) . , ESGI-. () . - . . : ; ' ; ' . – , , . ' . ESGI- , (Sustainable Reporting Platform, – SR-): , , , , . SR- MSCA4Ukraine, . . ESGI-, SR-. . - , , .
Keywords: M41; Q14; Q15; Q51; 330; climate-smart technologies; precision and organic farming; low-carbon and energy-saving technologies; ESGI report; post-war reconstruction of Ukrainian agribusiness; -; ESGI-